Exploring the Impact of Awareness, Tax Amnesty, and Socialization Efforts on Motor Vehicle Tax Compliance - Widhiartha Pratama, I Wayan Yoghi; Rasmini, Ni Ketut; Supadmi, Ni Luh; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 34 No 11 (2024)DO - 10.24843/EJA.2024.v34.i11.p12, 2024)
As governmental needs for funds increase alongside developmental demands, there is a concerning lag in taxpayer compliance, especially noted in the context of rising vehicle registrations. This study aims to examine the impact of awareness, tax amnesty, and tax socialization on motor vehicle taxpayer compliance at the Badung SAMSAT Office. The sample comprised 100 registered motor vehicle taxpayers from the Badung Regency SAMSAT Office in 2022. Results indicate that tax socialization, tax amnesty, and taxpayer awareness significantly enhance compliance with motor vehicle tax obligations at the Badung SAMSAT Office. This research contributes to the literature by providing empirical insights into how awareness, tax relief, and tax socialization influence motor vehicle taxpayer compliance at the specified location.